Harvard Business Review on Managing Your Career in Tough Times - Harvard Business School Publishing Corporation (Harvard Business Review Book, 2010)
In a challenging economy, managers have to be more thoughtful and strategic than ever about managing their careers. Charting your course to career success requires smart decision making and critical planning today. In this collection of articles from "Harvard Business Review", you'll get the essential advice you need to keep your career on track in tough times and beyond. "The Harvard Business Review Paperback Series" is designed to bring today's managers and professionals the fundamental information they need to stay competitive in a fast-moving world. From the preeminent thinkers whose work has defined an entire field to the rising stars who will redefine the way we think about business, here are the leading minds and landmark ideas that have established "Harvard Business Review The Harvard Business Review Paperback series is designed to bring today's managers and professionals the fundamental information they need to stay competitive in a fast-moving world. From the preeminent thinkers whose work has defined an entire field to the rising stars who will redefine the way we think about business, here are the leading minds and landmark ideas that have established Harvard Business Review as required reading for ambitious businesspeople in organizations around the globe.